From Sustainability to Profit: The Role of Green Accounting and ESG in the Banking Sector - Djasuli, Mohamad; Nuris Lestari, Anita; Zahra Ayu, Fatimatus; Choirur Rizki, R.; Syamsuddin, Syamsuddin (DINASTI RESEARCH, 2025)
This study examines the effects of Green Accounting and Environmental, Social, and Governance (ESG) disclosure on financial performance and firm value in Indonesian banks from 2022 to 2024. Sustainability has gained attention due to regulatory requirements and stakeholder expectations, but its financial impact in banking is not well understood. Using a quantitative panel data approach, secondary data from annual reports, sustainability reports, financial statements, and market sources were analyzed. Classical assumption tests ensured model validity, and the Common Effect Model with robust clustered standard errors addressed heteroskedasticity and autocorrelation. Results reveal that Green Accounting has a positive but insignificant effect on Return on Assets, while ESG disclosure has a positive and significant effect on financial performance when examined jointly with Green Accounting. Neither Green Accounting nor ESG disclosure significantly affects market valuation measured by Tobin’s Q. The findings suggest that sustainability practices improve internal financial outcomes but have limited impact on investor perceptions. Banks are encouraged to enhance ESG measurement and disclosure quality, integrate ESG into KPIs and management incentives, and adopt standardized reporting with external assurance mechanisms.